Formulation and Evaluation of Simvastatin Fast Dissolving Tablets with Croscarmellose Sodium as Super Disintegrant - Ramana Reddy, G.V.; Vidyadhara, S.; Anusha, Ch. (Asian Journal of Chemistry, 2011)
The objective of the present study is to formulate solid dispersions of simvastatin to improve the aqueous solubility and dissolution rate to facilitate faster onset of action. Solid dispersion of simvastatin with croscarmellose sodium (CCS), were prepared and compressed as tablets by using diluents such as spray dried lactose, dicalcium phosphate (DCP) and microcrystalline cellulose (MCC). The solid dispersion of simvastatin with croscarmellose sodium at different ratios were prepared by physical mixing, solvent evaporation and kneading methods. These were found to release drug faster than the pure drug in dissolution media. The rapid release of poorly soluble simvastatin from solid dispersions was influenced by the proportion of polymer and the method employed for its preparation. Among the three methods employed solvent evaporation and kneading methods were found to be suitable for improving the dissolution rate of simvastatin. The release was found to follow the first order kinetics. Some of the dispersions prepared by solvent evaporation and kneading method were further formulated in to a tablet with diluents such as spray dried lactose, dicalcium phosphate and microcrystalline cellulose. All the tablet preparations containing diluents were found to release drug in order of dicalcium phosphate > microcrystalline cellulose > spray dried lactose. The dissolution rate of such tablet formulations were found to release drug at a faster rate than that of tablets prepared with plain drug.